2009
DOI: 10.1063/1.3264949
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of complex behavior in gelling systems starting from simple behavior of single clusters

Abstract: A theoretical and numerically study of dynamical properties in the sol-gel transition is presented. In particular, the complex phenomenology observed experimentally and numerically in gelling systems is reproduced in the framework of percolation theory, under simple assumptions on the relaxation of single clusters. By neglecting the correlation between particles belonging to different clusters, the quantities of interest (such as the self intermediate scattering function, the dynamical susceptibility, the Van-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Recent theoretical and simulation studies by Fierro et al [23,32] showed that the dynamics of permanent gels was also non-Gaussian at Fickian time scales and verified systematically that such non-Gaussian dynamics could be understood as a linear combination of the Gaussian displacement distribution functions of different values of D s , where D s is the diffusion coefficient of cluster size s of permanent gels. By employing the percolation theory and assuming the relation between D s and s, they proposed a quantitative theory to explain the complex dynamic behavior of gels in terms of P (D s ) and compared the theory to their simulation results.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Recent theoretical and simulation studies by Fierro et al [23,32] showed that the dynamics of permanent gels was also non-Gaussian at Fickian time scales and verified systematically that such non-Gaussian dynamics could be understood as a linear combination of the Gaussian displacement distribution functions of different values of D s , where D s is the diffusion coefficient of cluster size s of permanent gels. By employing the percolation theory and assuming the relation between D s and s, they proposed a quantitative theory to explain the complex dynamic behavior of gels in terms of P (D s ) and compared the theory to their simulation results.…”
Section: Introductionmentioning
confidence: 86%
“…Such dynamic heterogeneity has been described in terms of the distribution τ or the distribution P (D) of diffusion coefficients D [22][23][24][25]. It is, however, usually formidable to obtain P (D): (1) in ergodic systems there is no distribution of D, i.e., P (D) reaches a δ function after sufficient time averaging, and (2) in nonergodic systems such as glasses the diffusion is usually too slow to estimate P (D).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explicitly obtain the scaling function we introduce a percolation approach elaborating on the cluster formulation used to describe the sol-gel transition [13]. We posit that our reference glassy system can be described as a collection of clusters each of which decays exponentially in time over a timescale t s that increases with the cluster size s. Structure and relaxation of clusters evidently depend on the precise nature of the system interaction and the underlying microscopic dynamics.…”
mentioning
confidence: 99%
“…Indeed, the chemical sol-gel transition shows the same continuous nature of the random percolation transition. Recently, it has been shown that the same cluster mechanism holds generally for gelling systems [3] and Mode Coupling Theory (MCT) schematic model A [4]. In particular, in Ref.…”
Section: Introductionmentioning
confidence: 89%